2022
DOI: 10.1136/bmjsem-2022-001418
|View full text |Cite
|
Sign up to set email alerts
|

Time cost associated with sports participation for athletes with high support needs: a time-motion analysis of tasks required for para swimming

Abstract: ObjectivesPeople with cerebral palsy and high support needs (CP&HSN) are profoundly inactive but also under-represented in studies evaluating physical activity interventions. Reasons for their exclusion have not been evaluated. We hypothesised that CP&HSN would be associated with high time costs of preparatory activities (eg, getting dressed/undressed), possibly contributing to low participation and under-representation. Accordingly, this pilot study aimed to: (1) evaluate whether the time required for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…Methodologically, the SCED used was ideally suited to the study aims. The design generated high-level evidence14 and conferred a range of advantages10 including permitting the allocation of time and expertise required to safely supervise participants with severe primary impairments and multiple comorbidities who were at increased risk of serious adverse events (see table 1); providing personalised assistance to alleviate the increased time cost associated with training12 and providing the methodological freedom to individualise training type, duration and intensity without compromising experimental control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methodologically, the SCED used was ideally suited to the study aims. The design generated high-level evidence14 and conferred a range of advantages10 including permitting the allocation of time and expertise required to safely supervise participants with severe primary impairments and multiple comorbidities who were at increased risk of serious adverse events (see table 1); providing personalised assistance to alleviate the increased time cost associated with training12 and providing the methodological freedom to individualise training type, duration and intensity without compromising experimental control.…”
Section: Discussionmentioning
confidence: 99%
“…Investigating whether performance-focused swimming training prevents motor decline in people with CPHSN presents considerable challenges. Severe functional limitations increase the time cost of participation for people with CPHSN by 8–13 times,12 significantly increasing research costs. Further, the heterogeneity that characterises CP is greatest in this population, who are often affected by a greater number of comorbidities that are more severe13 and many of these comorbidities (eg, seizure disorders, eating and drinking difficulties and pain) act as independent prognostic variables in exercise training trials.…”
Section: Introductionmentioning
confidence: 99%
“…A recent qualitative study 34 reported ‘accessible and accommodating environments’ took many forms, including physical access, practical supports, reasonable accommodations/adjustments, and positive attitudes towards disability. Another recent study described the supports required for people with complex CP to successfully access a community‐based exercise facility, and highlighted significant additional time requirements from all stakeholders 35 . Adapted equipment is frequently needed by people with disabilities which may limit their ability to engage without initial assistance or financial support to explore or implement equipment solutions or both.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study described the supports required for people with complex CP to successfully access a community‐based exercise facility, and highlighted significant additional time requirements from all stakeholders. 35 Adapted equipment is frequently needed by people with disabilities which may limit their ability to engage without initial assistance or financial support to explore or implement equipment solutions or both. Options for sustainable community physical activity for adults with complex CP therefore requires not only physically accessible venues but also those where reasonable adjustments are made to the environment, and where staff and other participants are accepting, supportive, and not time‐limited.…”
Section: Discussionmentioning
confidence: 99%